The Safety and Effectiveness of mRNA Vaccines in Large-scale Vaccination: A Systematic Review Based on COVID-19 and Flu Vaccines - Tan, Jingni (Exploring Science Academic Conference Series, 2026)
The COVID -19 pandemic has driven the large -scale deployment of mRNA vaccines. Despite the positive outcomes observed in initial clinical trials, in-depth, comprehensive assessments of the safety and efficacy of these vaccines across different populations r emain necessary following mass vaccination. This systematic review focuses on mRNA vaccines against COVID -19 and influenza, evaluating vaccine safety by analyzing post-vaccination adverse events and assessing efficacy by examining immunogenicity dynamics and protective effects against clinical endpoints. The findings indicate that these vaccines have high initial efficacy but wane over time, necessitating booster doses. The overall safety profile is favorable, with injection site reactions and systemic symptoms as the most common adverse reactions, and the incidence of rare adverse events shows age- and gender -related disparities. This study provides a reference for public health decision -making and vaccine development.